Obstacles and Strategies for Implementing the Merdeka Belajar Kampus Merdeka Curriculum at Theological College X - Raditia Christine Senjaya; Hotmaulina Sihotang; Lisa Gracia Kailola (LPPM Institut Pendidikan Nusantara Global, 2026)
Education in Indonesia is continuously evolving through curriculum development based on the Indonesian National Qualifications Framework (KKNI). One of the latest initiatives is the Merdeka Belajar Kampus Merdeka (MBKM), introduced in response to the COVID-19 pandemic and centred on the concept of Merdeka Belajar (Independent Learning). However, implementing the Merdeka Belajar Kampus Merdeka Curriculum in Theological Colleges (Sekolah Tinggi Teologi) faces several challenges, including a limited understanding of educational regulations, inadequate human resources, and insufficient funding. This study employs a qualitative, phenomenological approach to analyse the barriers faced by Sekolah Tinggi Teologi X in implementing the Merdeka Belajar Kampus Merdeka (MBKM) program. The results indicate that several aspects of MBKM are implementable, including: Lectures outside the primary study program, field service practice (PPL), an assessment system that does not require mandatory mid-semester or final exams. Conversely, other components remain difficult to execute, such as student exchange programs, entrepreneurship initiatives, and independent studies or projects. This study recommends that stakeholders analyse self-training strategies, evaluate the current curriculum, and develop a partnership strategy to accelerate the implementation of the Merdeka Curriculum in Theological Colleges.